2014
DOI: 10.1002/jssc.201400648
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic approach for the purification of nucleotides with magnetic separation

Abstract: The isolation of β-nicotinamide adenine dinucleotide is of great importance since it is widely used in different scientific and technologic fields such as biofuel cells, sensor technology, and hydrogen production. In order to isolate β-nicotinamide adenine dinucleotide, first 3-aminophenyboronic acid functionalized magnetic nanoparticles were prepared to serve as a magnetic solid support and subsequently they were used for reversible adsorption/desorption of β-nicotinamide adenine dinucleotide in a batch fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Equilibrium was reached after 45 min. This can be explained by the large number of available vacant sites on the RMBAG‐SCMPs surfaces, which are gradually occupied in time as a result of the sorption process . The sorption order is S ‐MA > R ‐MA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equilibrium was reached after 45 min. This can be explained by the large number of available vacant sites on the RMBAG‐SCMPs surfaces, which are gradually occupied in time as a result of the sorption process . The sorption order is S ‐MA > R ‐MA.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, nanoparticles have received more and more attention for separation purposes. Nanoparticles have large specific surface areas; thus, a large fraction of active sites are available for appropriate chemical interaction . In the numerous nanoparticles, magnetic nanoparticles have been widely researched because of their magnetic properties.…”
Section: Methodsmentioning
confidence: 99%
“…MNPs were prepared by co-precipitation method as reported in our previous work [25,26]. One gram Fe 3 O 4 nanoparticles were washed with ethanol and dispersed in a solution with 165-mL mineral oil and 2-mL tween-80; then, 10-g chitosan was completely dissolved by stirring in a solution of 1.0 dm 3 , 1.5 wt% acetic acid.…”
Section: Preparation Of Cross-linked Magnetic Chitosan Nanoparticlesmentioning
confidence: 99%
“…During an adsorption process, adsorption kinetics control, the solute uptake rate and characterize the adsorption proficiency of the adsorbents. Here adsorption kinetics of Pb 21 and Hg 21 on GQDs|QS were investigated by pseudo-first order model, pseudo-second-order model, and Elovich diffusion models [34,35]. The experimental results showed that the best adsorption kinetic model for the adsorption of Pb 21 and Hg 21 on GQDs|QS could be described by pseudosecond-order model ( Table 2).…”
Section: Adsorption Kinetics Studiesmentioning
confidence: 99%